Strategy of Pattern Partnership In Business and Micro, Small and Medium Enterprises (MSMEs) at One-Stop Integrated Service and Investment Office of South Kalimantan, Indonesia - Achmad Purwanto; Samahuddin Muharram; Setia Budhi; Andi Tenri Sompa (International Journal of Politic, Public Policy and Environmental Issues, 2021)
Micro, Small, and Medium Enterprises (MSMEs) have a contribution to the economy and safety net, especially for low-income people to productive economic activities. MSMEs are faced with several problems, namely the low quality of resources, capital, and product results. The pattern of the partnership between the business world and Micro, Small, and Medium Enterprises (MSMEs) conducted by the Investment Office and One Door Integrated Service of South Kalimantan Province is a form of government responsibility to empower and business development by facilitating business partnerships and MSMEs. This study aims to analyze the partnership strategy and the inhibiting factors of partnership based on a SWOT analysis conducted at the Office of Investment and One-Stop Integrated Services, Kalimantan Province. South. The research method is descriptive qualitative and the data sources used are primary data and secondary data. Data collection techniques are observation, interviews, and documentation, while the analytical tool used is the SWOT analysis. The results of the study show that the partnership pattern strategy has been running optimally with the principles of partnership, namely equality, transparency, and mutual benefit. The obstacles faced are the low quality of human resources, capital, and MSME products themselves. After using the SWOT analysis, the researcher proposes that the partnership budget be a priority scale for the budget for official activities, collaborate with other Regional Apparatus Organizations (OPD) and investment companies so that partnership programs are sustainable, and provide training to improve the quality of people and MSME products.